Standardizing Laryngeal Cleft Evaluations: Reliability of the Interarytenoid Assessment Protocol. (16th October 2018) - Coppess, Steven; Padia, Reema; Horn, David; Parikh, Sanjay R.; Inglis, Andrew; Bly, Randall; Dahl, John; Dudley, Daniel; Johnson, Kaalan
Abstract : Objective: While the Benjamin‐Inglis classification system is widely used to categorize laryngeal clefts, it does not clearly differentiate a type 1 cleft from normal anatomy, and there is no widely accepted or validated protocol for systematically evaluating interarytenoid mucosal height. We sought to propose the interarytenoid assessment protocol as a method to standardize the description of the interarytenoid anatomy and to test its reliability. Study Design: Retrospective review of endoscopic videos. Setting: Pediatric academic center. Subjects and Methods: The interarytenoid assessment protocol comprises 4 steps for evaluation of the interarytenoid region relative to known anatomic landmarks in the supraglottis, glottis, and subglottis. Thirty consecutively selected videos of the protocol were reviewed by 4 otolaryngologists. The raters were blinded to identifying information, and the video order was randomized for each review. We assessed protocol completion times and calculated Cohen's linear‐weighted κ coefficient between blinded expert raters and with the operating surgeon to evaluate interrater/intrarater reliability. Results: Median age was 4.9 years (59 months; range, 1 month to 20 years). Median completion time was 144 seconds. Interrater and intrarater reliability showed substantial agreement (interrater κ = 0.71 [95% confidence interval (CI), 0.55‐0.87]; intrarater mean κ = 0.70 [95% CI, 0.59‐0.92/rater 1, 0.47‐0.85/rater 2]; P <. 001). Comparing raters to the operating surgeon demonstrated substantial agreement (mean κ = 0.62; 95% CI, 0.31‐0.79/rater 1, 0.48‐0.89/rater 2; P <. 001). Conclusion: The interarytenoid assessment protocol appears reliable in describing interarytenoid anatomy. Rapid completion times and substantial interrater/intrarater reliability were demonstrated. Incorporation of this protocol may provide important steps toward improved standardization in the anatomic description of the interarytenoid region in pediatric dysphagia.